Does the Nutritional Composition of Dairy Milk Based Recovery Beverages Influence Post-exercise Gastrointestinal and Immune Status, and Subsequent Markers of Recovery Optimisation in Response to High Intensity Interval Exercise? - Russo, Isabella; Della Gatta, Paul A.; Garnham, Andrew; Porter, Judi; Burke, Louise M.; Costa, Ricardo J. S. (Frontiers in Nutrition, 2021)
This study aimed to determine the effects of flavoured dairy milk based recovery beverages of different nutrition compositions on markers of gastrointestinal and immune status, and subsequent recovery optimisation markers. After completing 2h high intensity interval running, participants (n=9) consumed a whole food dairy milk recovery beverage (CM, 1.2 g/kg body mass (BM) carbohydrate and 0.4g/kg BM protein) or a dairy milk based supplement beverage (MBSB, 2.2g/kg BM carbohydrate and 0.8g/kg BM protein) in a randomised crossover design. Venous blood samples, body mass, body water, and breath samples were collected, and gastrointestinal symptoms (GIS) were measured, pre- and post-exercise, and during recovery. Muscle biopsies were performed at 0h and 2h of recovery. The following morning, participants returned to the laboratory to assess performance outcomes. In the recovery period, carbohydrate malabsorption (breath H2 peak: 49 ppm vs 24 ppm) occurred on MBSB compared to CM, with a trend towards greater gut discomfort. No difference in gastrointestinal integrity (i.e., I-FABP and sCD14) or immune response (i.e., circulating leukocyte trafficking, bacterially-stimulated neutrophil degranulation, and systemic inflammatory profile) markers were observed between CM and MBSB. Neither trial achieved a positive rate of muscle glycogen resynthesis (-25.8 (35.5) mmol/kg dw/h). Both trials increased phosphorylation of intramuscular signalling proteins. Greater fluid retention (total body water: 86.9 % vs 81.9 %) occurred on MBSB compared to CM. Performance outcomes did not differ between trials. The greater nutrient composition of MBSB induced greater gastrointestinal functional disturbance, did not prevent the post-exercise reduction in neutrophil function, and did not support greater overall acute recovery.